1990
DOI: 10.1002/nme.1620300822
|View full text |Cite
|
Sign up to set email alerts
|

On numerical modelling of hot rolling of metals

Abstract: A transient, thermomechanical model, METFORM, based on viscoplasticity and heat and mass transport theories has been developed specifically for the prediction of the flow behaviour of metals during hot rolling. The coupling of metal flow, heat transport and microstructural changes is discussed and a framework to account for the coupling behaviour is formulated. The model is partially verified by experiments and is applied to the hot strip mill roughing process, with the focus of interest on skid mark effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In equation (4), T R is the work roll surface temperature that is simultaneously determined by another finite element analysis. 33 T ' is surrounding temperature and h con is the roll gap heat transfer coefficient.…”
Section: Heat Transfer and Deformation Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In equation (4), T R is the work roll surface temperature that is simultaneously determined by another finite element analysis. 33 T ' is surrounding temperature and h con is the roll gap heat transfer coefficient.…”
Section: Heat Transfer and Deformation Modelsmentioning
confidence: 99%
“…Regarding the published research works for simulating hot deformation processes such as hot rolling and hot forging it can be found that two main approaches have been adopted. The first approach deals with the macro modelling of the metal forming processes regardless of metallurgical phase transitions occurring and their influences on flow behaviour, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] while the second trend is concentrated on metallurgical phase transformations that happen in metal during or after hot deformation. [19][20][21][22][23][24][25][26] These studies have been mainly devoted to modelling the metallurgical aspect of hot deformation and development of constitutive equations.…”
Section: Introductionmentioning
confidence: 99%
“…A distributed surface flux, q fric , is also generated from frictional sliding. It increases rapidly near the entry and exit regions along the arc of contact and induces a dramatic change in the relative slip [8]. Its overall contribution to the thermal balance in the hot rolling process is low, but if it is considered, its value is determined as below [15]:…”
Section: Deformation Modelmentioning
confidence: 99%
“…Variation of temperature during hot rolling was investigated by Boguslaw and Cierniak [7] using a twodimensional finite difference model. Too [8] developed a coupled thermal and viscoplastic model using the control volume method for predicting the temperature and strain during hot rolling. The temperature distribution and metal flow during rough rolling were predicted by Chen et al [9] utilizing two-dimensional finite element and finite difference methods.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, temperature and velocity fields within the deforming metal may significantly affect these phenomena. There are many approaches for determining the temperature distribution and velocity field within the rolling metal, with most of these being based on numerical methods such as the finite element and the finite difference methods [1][2][3][4][5]. Recently, neural network has also become a popular tool for analysing problems in metal working, owing to its flexible learning capability.…”
Section: Introductionmentioning
confidence: 99%